If We Do Not Cut the Parables out of Their Frames - Gerhardsson, Birger (New Testament studies, 1991)
The New Testament discipline is a rather odd bird within the university. The object of our research is small, a book we can have in our pocket. And the learned work with this book has been carried out for a long time: acute theologians have studied it for almost two millennia and critical scholars for two centuries; there is hardly any counterpart. The secondary literature is as the grains of sand on the sea-shore.